Thermographic evaluation of the sinus areas of selected groups of students - pilot study - Ewelina Bryła; Maciej Dobrzyński; Krzysztof Dudek; Maciej Janeczek; Krzysztof Sobiech; Piotr Kosior; Anna Leśków; Małgorzata Tarnowska; Bożena Kaźmierska; Magdalena Wiśniewska; Ireneusz Całkosiński (Kazimierz Wielki University, 2017)
Thermal imaging technique is a sufficiently precise tool by which you can evaluate the condition of the blood supply of various areas of the body. Blood supply is connected with physiological functional status or ongoing pathological processes such as inflammation. The study was conducted on 40 volunteers - randomly selected students. The results are characterized by a slight standard deviation in maximum and minimum temperatures in the maxillary sinus area and the minimal difference between these results. On the basis of studies, the range of values of the reference temperature of the maxillary sinus. This range was isolated based on the results of a group of 39 individuals. It has been shown that in case of one person the results were not within the range of reference values indicating the presence of chronic inflammatory sinusitis.